Does authentic leadership stimulate organizational citizenship behaviors?: the importance of affective commitment as a mediator - Ribeiro, N.; Duarte, A. P.; Filipe, R.; David, R. (Sustainability Accounting, Management and Policy Journal, 2022)
This study sought to examine the impact of authentic leadership on employees’ organizational citizenship behaviors by investigating the mediating effect of affective commitment Data were collected on 194 leader-follower dyads in diverse organizations, using individual surveys. Followers reported their perceptions of authentic leadership and their affective commitment, and leaders assessed each follower’s level of organizational citizenship behavior. The results support the research hypotheses proposed, confirming that employees’ perceptions of authentic leadership are positively related to both their affective commitment and organizational citizenship behavior. Moreover, affective commitment completely mediates the relationship between authentic leadership and organizational citizenship behavior, indicating that authentic leaders increase employees’ affective bonds to their organization and, therefore, strengthen workers’ tendency to engage in organizational citizenship behaviors. Additional studies with larger samples are needed to clarify more fully not only authentic leadership’s influence on organizational citizenship behaviors but also other psychosocial variables affecting this relationship. The findings suggest that organizations can foster employees’ affective commitment and organizational citizenship behaviors by encouraging managers to adopt a more authentic leadership style. Authentic leaders are likely to focus the collective as they care about their teams, the wider organization, and even society’s welfare and sustainability. Growing concerns about sustainability and business ethics and the crisis of trust in organizations can be addressed through further research on positive leadership forms such as authentic leadership. This study’s findings suggest that authentic leadership fosters employees’ affective bond to organizations and their willingness to engage in organizational citizenship behaviors, which are two indicators related to organizational sustainability. This study integrated authentic leadership, affective commitment, and organizational citizenship behaviors into a single research model, thereby extending previous investigations. In addition, the data were collected from two sources (i.e., both leaders and followers in dyads) to minimize the risk of common-method variance.